Medical Specialty Choice and Effective Factors: A Cross-Sectional Survey of Last-Year Medical Students - Ghazal Mansouri; Zeinab Sadat Rooholamini; Fatemeh Karami Robati (Kerman University of Medical Sciences, 2023)
Background: Choosing a medical specialty is an important choice for medical students and the healthcare system.Objectives: This study aimed to investigate the interest of last-year medical students in choosing a future medical specialty and determine effective factors in it.Methods: A descriptive cross-sectional study of 201 medical students was performed in Iran in 2019. All medical students who completed the internship period by the end of September 2020 were selected by census method. A questionnaire was applied, the validity and reliability of which had already been registered in the Statistics Center of Afzalipour Hospital, Kerman, Iran. Data analysis was performed using descriptive methods, including frequency, percentage, mean, and standard deviation, and SPSS software (version 20). A significance level of P < 0.05 was considered statistically significant.Results: About 98% of students intended to choose a future medical specialty. The highest number of interested students were female (66%) and single (83.2%), with a mean age of 26.69 ± 12.22 years. The parents' educational level of most students interested in continuing education was a bachelor's degree or lower (52.3%). "Achieving a better economic position" (91.4%) was the most important factor for choosing a specialty. Most participants were interested in ophthalmology (18.2%). The factors "specific working hours" and "easy residency period" were indicated most frequently as effects on the preference for ophthalmology.Conclusion: The present findings provide significant insight into creating strategies to attract a number of medical students in other specialties based on the needs of the Iranian healthcare system.